On the Cramer-Rao bound for model-based spectral analysis. - Sando, S. (IEEE Signal processing letters)
We derive the Cramer-Rao bound for the parameters of a general time series model whose parameterization is dependent upon an unknown integer model order. To illustrate the usefulness of the theoretical results, the example of autoregressive spectral density estimation using Akaike (1974) order selection criterion is presented